I´m not a threat: A qualitative study on the mental health´s aspects of women living with HIV in Brazil (Research, Society and Development, 2024)
This study aimed to analyze aspects of the mental health of women living with Human Immunodeficiency Virus (HIV) in Brazil. To this end, was carried out qualitative research, anchored in the theoretical framework of Interpretive Anthropology, from January to March 2022, based on interviews with ten women living with HIV of reproductive age and undergoing treatment in a specialized public service in São Paulo, Brazil. Thematic Analysis was adopted as a methodological reference. Three thematic categories emerged from the data: Perception of the received care and its impact on mental health; Feelings related to living with HIV; and Perception of social stigma of HIV. The results showed that the mental health of women living with HIV was directly related to perceived health care, the information they receive, the way communication is established, and the bonds built in care. Feelings of fear, guilt and loneliness related to living with HIV and social stigma are elements that promote psychological suffering for these women. Sensitive and open strategies are essential to providing effective support and improving the lives of women living with HIV.